Dragon food : 70 legendary, magical, and fantasy-inspired recipes - Gallagher, Cayla (New York, NY : Skyhorse Publishing, 2024)
A dragon-themed cookbook with 70 recipes inspired by popular fantasy media. Recipes featured are desserts, drinks, and snack foods.
Enchanted forest -- Dragon's lair -- The magic market -- Under the sea -- Up in the clouds.
3-6
Includes index.
Keywords: Cooking; Dragons; Recipes; Cookbooks; Baking